Marker development using SLAF-seq and whole-genome shotgun strategy to fine-map the semi-dwarf gene ari-e in barley. (December 2016) - Jia, Qiaojun; Tan, Cong; Wang, Junmei; Zhang, Xiao-Qi; Zhu, Jinghuan; Luo, Hao; Yang, Jianming; Westcott, Sharon; Broughton, Sue; Moody, David; Li, Chengdao
Abstract Background Barley semi-dwarf genes have been extensively explored and widely used in barley breeding programs. The semi-dwarf geneari-e from Golden Promise is an important gene associated with some agronomic traits and salt tolerance. Whileari-e has been mapped on barley chromosome 5H using traditional markers and next-generation sequencing technologies, it has not yet been finely located on this chromosome. Results We integrated two methods to develop molecular markers for fine-mapping the semi-dwarf geneari-e : (1) specific-length amplified fragment sequencing (SLAF-seq) with bulked segregant analysis (BSA) to develop SNP markers, and (2) the whole-genome shotgun sequence to develop InDels. Both SNP and InDel markers were developed in the target region and used for fine-mapping theari-e gene. Linkage analysis showed thatari-e co-segregated with marker InDel-17 and was delimited by two markers (InDel-16 and DGSNP21) spanning 6.8 cM in the doubled haploid (DH) Dash × VB9104 population. The genetic position ofari-e was further confirmed in the Hindmarsh × W1 DH population which was located between InDel-7 and InDel-17. As a result, the overlapping region of the two mapping populations flanked by InDel-16 and InDel-17 was defined as the candidate region spanning 0.58 Mb on the POPSEQ physical map. Conclusions The current study demonstrated the SLAF-seq for SNP discovery and whole-genome shotgun sequencing for InDel development as an efficient approach to map complex genomic region for isolation of functional gene. Theari-e gene was fine mapped from 10 Mb to 0.58 Mb interval.